Trapped charged particles and fundamental interactions - Blaum, Klaus; Herfurth, Frank (Lecture Notes in Physics Ser., 2008)
Intro -- Low-Energy Precision Tests of Electroweak Theory -- R.G.E. Timmermans -- Beyond the Standard Model of Particle Physics -- The Search for Time-Reversal Violation -- Is the Neutrino Its Own Antiparticle? -- Atomic Parity Violation and the Weinberg Angle -- References -- Principles of Ion Traps -- G. Werth -- Trapping Principles -- Trap Techniques -- Ion Cooling Techniques -- Summary -- References -- Simulations for Ion Traps -- Methods and Numerical Implementation -- G. Zwicknagel -- Introduction -- Simulations of the Dynamics of Charged Particles -- Numerical Realization -- References -- Simulations for Ion Traps -- Buffer Gas Cooling -- S. Schwarz -- Introduction -- Damping and Mobility, Macroscopic Approach -- The Microscopic Picture -- Realistic Interaction Potentials -- Applications -- References -- Highly Charged Ions and High-Resolution Mass Spectrometry in a Penning Trap -- Sz. Nagy, K. Blaum, and R. Schuch -- Preface -- Brief Introduction to Highly Charged Ions -- Production of Highly Charged Ions -- Mass Measurement of Highly Charged Ions in a Penning-Trap Mass Spectrometer -- Cooling of Highly Charged Ions -- The Penning-Trap Mass Spectrometer Smiletrap -- Examples for Applications of High-Precision Atomic/Ionic Masses in Modern Physics -- Summary and Outlook -- References -- Fundamental Tests with Trapped Antiprotons -- E. Widmann -- A Brief History of Antimatter -- Low-Energy Antiproton Facilities -- Past, Present, and Future -- CPT Symmetry and Trapped Antiprotons -- Experimental Tests of CPT Using Antiprotons -- Summary -- References -- Index.